A parallel dual-type method for solving CWLS problem - Lin, Shieh-Shing (Electric power systems research, 2003)
In this paper, we propose a method to solve the distributed constrained state-estimation problem and discuss the associated implementation. This method includes a successive quadratic programming process and a parallel dual-type method possessing decomposition effects. With the decomposition, our method achieves a dramatic speed-up ratio compared with the commercial IMSL subroutines in solving CWLS problems.